2015
DOI: 10.3109/00498254.2014.1001809
|View full text |Cite
|
Sign up to set email alerts
|

Time and concentration dependency of P-gp, MRP1 and MRP5 induction in response to gemcitabine uptake in Capan-2 pancreatic cancer cells

Abstract: 1. Influx and efflux proteins play a major role in the overall uptake and efficacy of chemotherapeutic agents and cellular chemo-resistance. 2. The present study investigated the time course and dose dependency of the induction of three efflux proteins, P-gp, MRP1 and MRP5, in response to gemcitabine exposure in Capan-2 pancreatic cancer cell line at transcriptional and translational levels. The influence of exposure on the influx protein (ENT1), the net cellular uptake of the gemcitabine, the overall ATPase a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 29 publications
0
21
0
Order By: Relevance
“…Capan-2 pancreatic cancer cells, similar to many other type of cancerous cells, utilize various cellular mechanisms such as microparticle formation (51), and induction of efflux proteins against anticancer drugs (24). Several studies have shown that the resistance of pancreatic cancer cells to chemotherapeutics including gemcitabine, is the result of reduced cellular uptake via influx proteins (12) or their efficient removal from cells by efflux proteins (15,24).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Capan-2 pancreatic cancer cells, similar to many other type of cancerous cells, utilize various cellular mechanisms such as microparticle formation (51), and induction of efflux proteins against anticancer drugs (24). Several studies have shown that the resistance of pancreatic cancer cells to chemotherapeutics including gemcitabine, is the result of reduced cellular uptake via influx proteins (12) or their efficient removal from cells by efflux proteins (15,24).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that the resistance of pancreatic cancer cells to chemotherapeutics including gemcitabine, is the result of reduced cellular uptake via influx proteins (12) or their efficient removal from cells by efflux proteins (15,24). Synthetic antioxidants such as BHA and BHT are widely used in pharmaceutical products as well as in the food industry to protect susceptible chemicals against oxidation (27,28).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations